Solubility measurement, model evaluation and Hansen solubility parameter of piperonylonitrile in four binary solvents. (December 2020) - He, Haixia; Sun, Renren; Wan, Yameng; Jiang, Gaoliang; Sha, Jiao; Li, Yu; Li, Tao; Ren, Baozeng
Highlights: Solubility of piperonylonitrile was measured by laser monitoring method. The miscibility of piperonylonitrile in mixed solvents was revealed by Hansen solubility parameter. Experimental solubility was regressed and analyzed by four thermodynamic models. Mixing thermodynamic properties of piperonylonitrile were got by Wilson model. Abstract: The present research work proposed the mole fraction solubility and mixing thermodynamic properties of piperonylonitrile in different binary solvent mixtures such as ethanol + (acetone, 1, 4-dioxane, DMF and methyl acetate) at " T = 278.15 K to 323.15 K" and " p = 0.1 MPa". The results indicated that as the temperature and mass fraction of positive solvents increased, the measured solubility of piperonylonitrile increased in all mixtures considered. Analysis using Hansen solubility parameter revealed that the affinity between piperonylonitrile and all mixed solvents was related to multiple factors. The experimental solubility of piperonylonitrile in four binary solvent mixtures was regressed by employing four thermodynamic models such as UNIQUAC, Margules, Wilson and NRTL model. It was found that the Wilson model was accurate enough to correlate the experimental solubility. Moreover, the mixing thermodynamic properties of piperonylonitrile in different mixed solvents were also estimated and discussed according to the Wilson model and experimental data. The results of the negative Δ mix G values and positive Δmix S values demonstrated the entropy-driven and spontaneous mixing process of piperonylonitrile in all binary solvent mixtures.